Pathogenic diversity of Phytophthora sojae in the southeast of the Province of Buenos Aires - Grijalba, Pablo Enrique (2020)
Phytophthora sojae causes root and stem rot of soybeans. In Argentina, this pathogen has shown dramatic shifts in pathotype variability since its first discovery during the 1970s. The aim of this study was to report the presence and distribution of different pathotypes of P. sojae isolates from 2013 to 2015 in the southeast of Buenos Aires Province in Argentina. Isolates were obtained from diseased soybean plants and soil in contact with the infected root. The pathotype evaluation of P. sojae was determined with a set of eight differential soybean lines. One hundred and twenty-four P. sojae isolates were obtained and forty pathotypes were determined, which is a considerable variability for a relatively new and recently infested soybean area.